Credible Tendencies of Changes of Black Sea Level in ХХІ Age at Different Scenarios of Rise in a Temperature in an Arctic - Холопцев, А. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 1970)
The difference of the density water of the Labrador Current and Gulf Streamdecreases in consideration of modern warming in Arctic. It will lead to essential reduction of temperatures of the water on the surface of the Northern Atlanticand change of the climate of this region. This process will cause essential reduction of intensity of the precipitation in Ukraine, falling in winter and spring; will cause the attenuation of snow feeds of its rivers and artesian basins, degradation of its forests and essential changes of structure of the steppe phytocenosis.